2020
DOI: 10.3390/nu12020512
|View full text |Cite
|
Sign up to set email alerts
|

Nutrigenomics and Breast Cancer: State-of-Art, Future Perspectives and Insights for Prevention

Abstract: Proper nutrition plays a major role in preventing diseases and, therefore, nutritional interventions constitute crucial strategies in the field of Public Health. Nutrigenomics and nutriproteomics are arising from the integration of nutritional, genomics and proteomics specialties in the era of postgenomics medicine. In particular, nutrigenomics and nutriproteomics focus on the interaction between nutrients and the human genome and proteome, respectively, providing insights into the role of diet in carcinogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 118 publications
(165 reference statements)
0
11
0
Order By: Relevance
“…Additionally, epigenetic alterations in VDR and CYP24A1 have been linked to vitamin D resistance 48 . Individuals with malignancies that are positive for ER, VDR, and AR all have a better prognosis 49. These findings highlight the need of assessing VDR polymorphisms and steroid receptor status in breast cancer samples at the same time 50,51 .…”
Section: Heterogeneity In Vdr Expression Concerning Steroid Receptors...mentioning
confidence: 81%
“…Additionally, epigenetic alterations in VDR and CYP24A1 have been linked to vitamin D resistance 48 . Individuals with malignancies that are positive for ER, VDR, and AR all have a better prognosis 49. These findings highlight the need of assessing VDR polymorphisms and steroid receptor status in breast cancer samples at the same time 50,51 .…”
Section: Heterogeneity In Vdr Expression Concerning Steroid Receptors...mentioning
confidence: 81%
“…Comparing two diets that show varying levels of type and quantity of fat can help us resolve this matter. Western diets are known for having higher levels of saturated fat and trans fats than Mediterranean diets [12]. Mediterranean diets consisted of olive oil, vegetables, fruits, plant proteins, seafood, nuts, and low-fat dairy products, and had a fat composition that favored a higher amount of omega-3 and omega-6 PUFA [4,13].…”
Section: Fat Qualitymentioning
confidence: 99%
“…The fact that Mediterranean diets are typically high in fat due to high olive oil consumption emphasizes the importance of quality over quantity in fat consumption [1]. A meta-analysis showed that breast cancer-specific risk was reduced among those following the Mediterranean diet (RR = 0.93 and 95% confidence interval (CI) = 0.87-0.99) [12].…”
Section: Fat Qualitymentioning
confidence: 99%
“…Furthermore, new, emerging biomarkers have been discovered in the fields of genomics and proteomics, like exosomes, which are involved in the cellular cross-talks and related biological processes [16]. Nutrigenomics [17,18], epigenomics [19] and nutriepigenomics [20,21] investigate how dietary habits and nutrition, as well as environmental factors, and their complex, non-linear interactions can finely modulate the human genome and its expression, and impact on human diseases, including gynecological conditions. For instance, a study explored the relationship between folic acid supplementation and one carbon metabolism gene single nucleotide polymorphisms (SNPs) on small-for-gestationalage (SGA) births [17].…”
Section: Gynecology and Omics Datamentioning
confidence: 99%